Renal protective and immunoregulatory effects of Lactobacillus casei strain Shirota in nephropathy-prone mice - Chan, Chun-Wai; Chen, Yu-Ting; Lin, Bi-Fong (Frontiers in Nutrition, 2024)
The incidence of severe acute kidney injury (AKI) is considerably high worldwide. A previous study showed that gut microbial dysbiosis was a hallmark of AKI in mice. Whether the probiotic Lactobacillus casei strain Shirota (LcS) plays a role in kidney disease, particularly AKI, remains unclear. To investigate the effects of LcS on kidney injury, tubule-specific conditional von Hippel-Lindau gene-knockout C57BL/6 mice (Vhlhdel/del mice) were supplemented without (Ctrl) or with probiotics (LcS) in Experiment 1, and their lifespan was monitored. Additionally, the Vhlhdel/+ mice were supplemented without (Ctrl and AA) or with probiotics (LcS and LcS+AA) in Experiment 2. Probiotic LcS (1×10^9 colony-forming units) was supplemented once daily. After 4 weeks of LcS supplementation, AA and LcS+AA mice were administered aristolochic acid (AA; 4 mg/kg body weight/day)-containing purified diet for 2 weeks to induce AA nephropathy before sacrifice. The results showed that supplementation of LcS significantly prolonged the lifespan of Vhlhdel/del mice, suggesting a potential renal protective effect. AA induced-nephropathy increased not only the indicators of renal dysfunction and injury, including urinary protein and kidney injury molecule (KIM)-1, serum blood urea nitrogen (BUN) and creatinine, but also serum interleukin (IL)-6 levels, renal macrophage infiltrations, and pathological lesions in Vhlhdel/+ mice. LcS supplementation significantly reduced urinary protein and KIM-1 levels, serum BUN and IL-6 levels, and renal M1 macrophages, tissue lesions, and injury scores. We also found that LcS maintained gut integrity under AA induction and increased intestinal lamina propria dendritic cells. Furthermore, LcS significantly reduced pro-inflammatory IL-17A and upregulated anti-inflammatory IL-10 production by immune cells from intestinal Peyer’s patches (PP) or mesenteric lymph nodes (MLN), and significantly increased IL-10 and reduced IL-6 production by splenocytes. In conclusion, prior supplementation with probiotic LcS significantly alleviated the severity of renal injury. This renal protective effect was partially associated with the enhancements of intestinal and systemic anti-inflammatory immune responses, suggesting that LcS-induced immunoregulation might contribute to its renal protective effects.